2006
DOI: 10.1111/j.1464-410x.2007.06532.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cyclical oestrogen on bladder and urethral structure and function

Abstract: after Ovx, which remained in place for a subsequent 2-week period. Group 3 was then assessed after the 2 weeks on oestradiol. Groups 4 and 5 then had their oestradiol tablets removed for 2 weeks and group 4 was assessed after this period off oestradiol. Group 5 then received a new oestradiol tablet that was left in place for an additional 2 weeks. RESULTSBoth groups receiving oestrogen (3 and 5) had a statistically significantly greater bladder weight than both the control group and group 2. The volume fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
3
18
1
3
Order By: Relevance
“…The decrease in bladder perfusion in BPS/IC has been demonstrated in previous studies by conducting dual-canal endoscopic laser Doppler flow measurements [22,23]. In an experimental study, it has been shown that the decrease in estrogen levels, which has been proved to be protective against oxidative stress, causes blood flow to the bladder mucosa and muscles to decrease and thus causes oxidative stress of free radicals resulting from ischemia, hypoxia, and reperfusion [6].…”
Section: Discussionmentioning
confidence: 91%
“…The decrease in bladder perfusion in BPS/IC has been demonstrated in previous studies by conducting dual-canal endoscopic laser Doppler flow measurements [22,23]. In an experimental study, it has been shown that the decrease in estrogen levels, which has been proved to be protective against oxidative stress, causes blood flow to the bladder mucosa and muscles to decrease and thus causes oxidative stress of free radicals resulting from ischemia, hypoxia, and reperfusion [6].…”
Section: Discussionmentioning
confidence: 91%
“…Enfin, il a été montré que les estrogènes permettaient de prévenir, après la ménopause, la survenue de cystites [9], d'atrophie de l'appareil urinaire [ 38,39]. À l'inverse, après ovariectomie bilatérale ou à la naissance, lorsque le rat ou le lapin est traité d'emblée par estrogènes, apparaissent une hypertrophie de la paroi vésicale en rapport avec une augmentation des fibres musculaires lisses, une diminution de la teneur en collagène et une augmentation de la vascularisation de la vessie [33,34,37-41].…”
Section: Introductionunclassified
“…L'hypertrophie intéresse la partie mobile de la vessie. Elle s'accompagne d'une augmentation du poids de la vessie [31,37,38]. L'hypertrophie est probablement multifactorielle.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The result is a hypoxic condition which in turn mediates the generation and release of free radicals and oxidative damage to cellular and subcellular structures of the bladder [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%